2019
DOI: 10.1080/15384101.2019.1690883
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0000003 promotes the proliferation and metastasis of non-small cell lung cancer cells via miR-338-3p/insulin receptor substrate 2

Abstract: Background: Circular RNAs (circRNAs) play a pivotal regulatory role in a variety of tumors. Nevertheless, the detailed function of circ_0000003 in non-small cell lung cancer (NSCLC) and its regulatory mechanism remain elusive. Methods: RT-PCR was carried out to detect the expressions of circ_0000003, miR-338-3p and insulin receptor substrate 2 (IRS2)in NSCLC tissues. Besides, western blot was done to monitor IRS2 expression in NSCLC cells. The correlation between circ_0000003 and clinicopathologic characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Lung cancer is the major cause of cancer-associated death worldwide. Nearly 80% of lung cancer diagnoses are non-small-cell lung cancer (NSCLC) and the major subtypes are lung squamous cell carcinoma (LSCC) and lung adenocarcinoma (LUAD) [ 1 ]. Despite the great advances in the diagnostics, targeted drugs and immunotherapy, the overall survival (OS) remains unsatisfactory for patients with NSCLC owing to patients diagnosed with NSCLC had cancer cell diffusion and metastases [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is the major cause of cancer-associated death worldwide. Nearly 80% of lung cancer diagnoses are non-small-cell lung cancer (NSCLC) and the major subtypes are lung squamous cell carcinoma (LSCC) and lung adenocarcinoma (LUAD) [ 1 ]. Despite the great advances in the diagnostics, targeted drugs and immunotherapy, the overall survival (OS) remains unsatisfactory for patients with NSCLC owing to patients diagnosed with NSCLC had cancer cell diffusion and metastases [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…found that patients with non-small cell lung cancer (NSCLC) would further develop resistance to the available treatments by activating insulin-like growth factor-1 receptor (IGF1R) ( Hayakawa et al., 2020 ). In addition, itā€™s reported that INS plays an important role in the proliferation and metastasis of NSCLC cells ( Li S. et al., 2019 ). AKT is an important kinase in the PI3k-AKT pathway, which is catalyzed by PI3K to migrate to the cell membrane and activate ( Zhang et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are still some limitations to this project. CeRNA network circRNA/miRNA/mRNA in lung cancer was widely identified [ 6 , 7 , 32 , 33 ]. Therefore, the downstream mRNA of the circHIPK3/miR-381-3p axis is worthy of further exploration to enrich our cognition on the mechanism of circHIPK3 in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, circCMPK1 (hsa_circ_0012384) positively modulated cell proliferation of NSCLC cells by increasing cyclin D1 expression by sponging miR-302e [ 6 ]. Li et al reported that circ_0000003 could accelerate the progression of NSCLC by promoting the proliferation and metastasis via the miR-338-3p/IRS2 pathway [ 7 ]. Gao and his colleagues alleged that hsa_circ_0007059 inhibited lung cancer cell growth and epithelialā€“mesenchymal transition through the inhibition of miR-378 [ 8 ].…”
Section: Introductionmentioning
confidence: 99%